2019
DOI: 10.1021/acsbiomaterials.8b01456
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gradient and Offset Architectures on the Mechanical and Biological Properties of 3-D Melt Electrowritten (MEW) Scaffolds

Abstract: This study describes the fabrication and characterization of three-dimensional (3-D) poly­(ε-caprolactone) (PCL) scaffolds with defined pore architectures prepared using the melt electrowriting (MEW) technique. Three homogeneous pore-sized (250, 500, and 750 μm) scaffolds, two fiber offset (30/70% and 50/50%), and a three-layered (250 μm bottom–500 μm middle–750 μm top) gradient pore-sized scaffolds were designed and printed with ∼10 μm fibers. The mechanical properties (tensile and compression tests), total s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 49 publications
4
75
0
Order By: Relevance
“…Although higher porosity increased ALP activity, our results showed the offset scaffolds demonstrated superior matrix mineralization. This may be related to the surface wettability which increases surface free energy resulting in better cell attachment due to greater protein adsorption of ECM-products [44], and the rougher surface of the offset structures after calcium phosphate (CaP) coating modification, which was shown in our previous study by alizarin-red staining and surface area (BET) analysis [22]. It has been displayed the CaP coating on the surface of the fibres within the cells, that the higher level of mineralization was identified on the offset and then 250 μm scaffold structures through alizarin-red staining and micro-CT analysis.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Although higher porosity increased ALP activity, our results showed the offset scaffolds demonstrated superior matrix mineralization. This may be related to the surface wettability which increases surface free energy resulting in better cell attachment due to greater protein adsorption of ECM-products [44], and the rougher surface of the offset structures after calcium phosphate (CaP) coating modification, which was shown in our previous study by alizarin-red staining and surface area (BET) analysis [22]. It has been displayed the CaP coating on the surface of the fibres within the cells, that the higher level of mineralization was identified on the offset and then 250 μm scaffold structures through alizarin-red staining and micro-CT analysis.…”
Section: Discussionmentioning
confidence: 91%
“…Our previous studies have shown that, when compared to simpler homogeneous structures, scaffolds with offset and gradient architectures resulted in significantly higher cell proliferation following seeding (Additional file 1) [22]. As a logical extension of this work, this study will investigate the potential effects of heterogeneous porous scaffold architectures, particularly offset and gradient structures on osteogenic gene expression by osteoblasts seeded into these scaffolds and the rate of mineralization throughout the construct.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations